The Efficacy of Combined Cisplatin and Nanoparticle Albumin-Bound Paclitaxel in a Stage IV Pancreatic Squamous Cell Carcinoma Patient With a Somatic BRCA2 Mutation: A Case Report - Huang, Xiaozhun; Wang, Chunling; Ma, Teng; Huang, Zhangkan; Zhou, Houhong; Xu, Lin; Zhang, Renjie; Zhao, Jianjun; Zhang, Yefan; Huang, Zhen; Shao, Lin; Wang, Yang; et al. (Frontiers in Oncology, 2021)
Pancreatic squamous cell carcinoma (SCC) is a rare primary pancreatic malignancy with poor prognosis. The median overall survival (OS) for metastatic setting is only 4 months and the optimal management remains poorly defined. In the present study, we report a 52-year-old female patient with stage IV primary SCC of the pancreas harboring a deleterious BRCA2 somatic mutation. After 10 cycles of chemotherapy of cisplatin combined with nanoparticle albumin-bound paclitaxel, metastatic lesions in liver and lymph nodes achieved radiographic complete responses and pancreatic lesion shrank from 5.7 cm to 1.5 cm in diameter. The patient subsequently underwent a posterior radical antegrade modular pancreatosplenectomy with R0 resection and residual liver lesions were also resected. After 3 months, a tumor relapsed in liver. She was then treated with olaparib combined with pembrolizumab and achieved stable disease on liver lesion. The patient eventually died from cerebral hemorrhage with a long OS of 21 months. Our case demonstrated a favorable clinical activity and survival advantage of the combined cisplatin and nanoparticle albumin-bound paclitaxel, which might serve as therapeutic option for patient with BRCA-mutant pancreatic SCC.